Sistem Pakar Diagnosa Kelainan Sistem Ortopedi pada Manusia dengan Metode Forward Chaining dan Dempster Shafer: Expert System for Diagnosing Abnormalities of Human Orthopedics System using forward chaining and Dempster Shafer Method - Nurhaini Rahmawati; Fitri Bimantoro (Informatics Engineering Dept., Faculty of Engineering, University of Mataram, 2021)
The bones and skeleton are very important parts of orthopedics and are the most vulnerable parts of the body. One of the obstacles in the diagnosis of orthopedic disorders is the distance from the hospital and the few orthopedic doctors. This study developed an expert system that runs on an Android-based smartphone to diagnosa 13 types of abnormalities in the orthopedic system with 92 symptom input based on the knowledge of 3 experts using the forward chaining and dempster shafer methods to obtain conclusions about the type of orthopedic disorder suffered. Based on the test results with theoretical calculations, it is found that the system calculation results are in accordance with the results of manual calculations. In testing the accuracy of the system, from 30 examples of cases tested on 3 experts, the accuracy value was obtained based on the average expert weight of 81.11%, the weight of each expert in sequence is 80.00% for expert 1, 83.33% for expert 2, and 73.33% for expert 3, where this accuracy value shows that the performance of the dempster shafer method in diagnosing orthopedic disorders is good and it can be said that the dempster shafer method suitable to be applied in cases of orthopedic disorders. The MOS (Mean Opinion Score) test on 30 respondents resulted in an MOS value of 4.45 from a scale of 5 which indicates that the system is feasible to use and is categorized into a good system